Mammal fauna in Phong Nha Ke Bang-Hin Nam No region: the species diversity and conservation significance - Dang, Nguyen Xuan; Nghia, Nguyen Xuan (Academia Journal of Biology, 2018)
Phong Nha Ke Bang-Hin Nam No Region (PNKB-HNN Region) is  one of the world largest limestone conservation landscapes which contains the universal outstanding values on biodiversity and high diversity of flora and fauna. This paper reviews results of mammal biodiversity surveys conducted from 1970s to 2017 in PNKB-HNN region to give more comprehensive evaluation of the fauna diversity and conservation significance. The review shows that up to date, 150 mammal species from 32 families and 11 orders have been recorded in PNKN-HNN region. The highest diversity is order Chiroptera (54 species), then follow orders Rodentia (35 species), Carnivora (30 species), Primates (11 species), Artiodactyla (8 species), Soricomorpha (4 species). Other orders (Pholidota, Erinaceomorpha, Lagomorpha, Scandentia and Dermoptera) have only 1–2 species each.  PNKB NP alone contains 143 species belonging to 32 families and 11 orders while HNN NCA contains 75 species belonging to 32 families and 11 orders.         PNKB-HNN region is the home of 56 mammal species of conservation priority including 41 species enlisted in 2017 IUCN Red List, 46 species enlisted in 2007 Vietnam Red Data Book. Out of 41 species enlisted in 2017 IUCN Red List, 3 species are at Critically Endangered category (CR), 9 species at Endangered category (EN), 16 species at Vulnerable category (VU), 10 species are at Near Threatened category (NT) and 3 species are of Deficient Data (DD). Out of 46 species enlisted in Vietnam Red Data Book, 3 species are at CR, 19 species at EN, 21 species at VU, 2 species at LR and 1 Species of DD.PNKB NP alone harbors 54 species of conservation priority including 40 globally threatened species, 45 nationally threatened species, 40 species under Governmental Decree No. 32/2006/ND-CP and 24 species under Governmental Decree No. 160/2013/ND-CP. HNN NCA contains 39 species of conservation priority including 32 species enlisted in 2017 IUCN Red List and 34 species enlisted in 2007 Vietnam Red Data Book. The most notable conservation priority species in PNKB-HNN are Ha Tinh Langur Trachypithecus hatinhensis, Red-shanked Douc Pygathrix nemaeus, Laotian Black Langur Trachypithecus laotum, Southern White-cheeked Gibbon Nomascus siki, Malaysian Bear Helarctos malayanus, Sun Bear Ursus thibetanus, Chinese Serow Capricornis milneedwardsii, Annamite Striped Rabbit Nesolagus timminsii and Laotian Rock Rat Laonastes aenigmamus. Moreover, PNKB-HNN region is the only home of Laotian Rock Rat Laonastes aenigmamus and Lao Limestone Rat Saxatilomys paulinae.